The Impact of Digital Learning Policies on Educational Equity in Rural Indonesian Schools - Yuli Endang Lestari; Yuslim Alif Pudin; Vishnu Murti Wibowo (International Journal of Educational Evaluation and Policy Analysis, 2024)
This study examines the effects of digital learning policies implemented in rural Indonesian schools on educational equity. By analyzing policy documents, teacher interviews, and student performance data from multiple rural regions, this research identifies key factors that facilitate or hinder equitable access to digital education. Findings reveal that while digital learning policies have the potential to improve educational access, disparities in infrastructure and digital literacy remain significant challenges. Recommendations for policymakers focus on strategies to address these gaps and enhance policy effectiveness.